Madrasah: dari Nizamiyah hingga Pesisiran Jawa - Junaedi, Mahfud (FITK UIN Walisongo, 2014)
Growth and development in the Coastal Java madrasah in the early twentieth century until now generally spearheaded by scholars/religious leaders who graduated in Islamic centers in the Middle East. At first they established the boarding school, followed by the establishment of madrasah to the coast of Javacan be regarded as children of a boarding school. The educational institutions have bonding formation of madrasah was first built byÂ Nizam al-Mulk in Baghdad in 1057, later known as madrasahÂ Nizamiyah . This school is an educational institution that aims to teach Fiqh Sunni schools. Institutions of higher education has become one of the eleventh century and became the blueprint for the development of similar madrasah in the Islamic world. Historically, madrasah in Java can not be separated from the Middle East, especially the relationshipHaramayn scholars of al-Azhar and Cairo with the students in Java, Indonesia.AbstrakPertumbuhan dan perkembangan madrasah di Pesisir Jawa pada awal abad ke XX hingga kini, umumnya dipelopori oleh para kiai atau tokoh agama yang menamatkan pendidikan di pusat-pusat Islam tersebut. Pada awalnya mereka mendirikan pondok pesantren, lalu diikuti dengan pendirian madrasah, sehinggamadrasah di pesisir Jawa bisa dikatakan sebagai anak-anak pesantren. Lembaga pendidikan ini memiliki ikatan dengan madrasah pertama kali dibangun oleh Nizam al-Mulk di Baghdad pada tahun 1057, kemudian dikenal dengan madrasahNizamiyah. Madrasah ini merupakan lembaga pendidikan yang bertujuan untuk mengajarkan fikih mazhab Sunni. Lembaga pendidikan tinggi ini ada pada abad kesebelas dan menjadi cetak biru bagi pengembangan madrasah-madrasah serupadi dunia Islam. Secara historis, keberadaan madrasah di Jawa tidak dapat dipisahkan dari hubungan ulama Timur Tengah, khususnya Haramayn dan al- Azhar Kairo dengan para murid di Jawa, Indonesia.Â ",